2012
DOI: 10.1002/anie.201205744
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Coordination Chemistry of Phosphorus(I) Zwitterions

Abstract: Go for the gold! Incorporating a borate anion into the backbone of a triphosphenium cation produces a unique zwitterionic phosphanide that can coordinate to one or two {AuCl} fragments depending on the steric bulk of the ligand (see picture; Au yellow, P purple, Cl green). Computational investigations show that in this μ-type ligand, the phosphorus atom behaves only as a σ,π donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 69 publications
4
54
0
Order By: Relevance
“…The solid‐state structure of 8 showed that one phosphorus atom coordinated to two gold centers leaving the other phosphorus atom uncoordinated (Figure c). This coordination behavior is typical for phosphorus‐centered zwitterions, as reported by Ragogna et al . and Bertrand et al .…”
Section: Resultssupporting
confidence: 81%
“…The solid‐state structure of 8 showed that one phosphorus atom coordinated to two gold centers leaving the other phosphorus atom uncoordinated (Figure c). This coordination behavior is typical for phosphorus‐centered zwitterions, as reported by Ragogna et al . and Bertrand et al .…”
Section: Resultssupporting
confidence: 81%
“…In contrast to the coordination chemistry of phosphides [22] and recent reports on complexes of related neutral ligands featuring [X-P(I)-X] (X = C, P) [23] fragments, the coordination chemistry of cations similar to 13 + has not yet been 5 tht), a very broad singlet is observed (d(P) = À67.2 ppm, Dn 1/2 = 210 Hz, compare with 13[OTf]: d(P) = À66.1 ppm, Dn 1/2 = 6 Hz). The broadening is attributed to the fast quadrupole relaxation of the 63 Cu nucleus (I = 3/2).…”
mentioning
confidence: 94%
“…The lack of progress in this area is likely attributable to the weak ligating ability of these and other cationic phosphanido species. As an example, analogous triphosphenium cations require the inclusion of an anionic group to their framework in order for them to form isolable metal complexes . In this case, the increased ligating ability may be rationalised by destabilisation of the frontier orbitals due to reduced negative hyperconjugation (π‐backbonding) from the P I centre into the flanking phosphines and the removal of the overall positive charge.…”
Section: Introductionmentioning
confidence: 99%